Bone Quality and Fracture-Healing in Type-1 and Type-2 Diabetes Mellitus. (7th August 2019) - Henderson, Shasta; Ibe, Izuchukwu; Cahill, Sean; Chung, Yeon-Ho; Lee, Francis Y.
Abstract : Patients with type-1 or type-2 diabetes have an increased risk of fracture, which is secondary to early bone loss in type-1 diabetes whereas, in type 2, the development of abnormal osseous architecture results in paradoxically increased or normal bone mineral density. Diabetic patients diagnosed with osteoporosis should receive the same standard antiresorptive therapies as non-diabetic patients in conjunction with appropriate glycemic control. Medical management of type-2 diabetes can affect bone health and fracture risk. Thiazolidinediones have been correlated with an increased facture risk, whereas metformin can be protective of the bone health of diabetic patients. Diabetes increases the likelihood of nonunion and delayed union of fractures as well as other perioperative complications such as infection. Perioperative glycemic control may decrease the risk of perioperative complications, especially surgical site infection. Methods to directly improve diabetic fracture-healing such as the use of parathyroid hormone and sclerostin antibody are in the experimental phase. Prior to proceeding with operative intervention for fractures, it is necessary to consider the additional risk posed by diabetes, which must be taken into account when planning the approach, fixation, and postoperative management in this population.